Does the Artery-first Approach Improve the Rate of R0 Resection in Pancreatoduodenectomy? A Multicenter, Randomized, Controlled Trial - Sabater, Luis; Cugat, Esteban; Serrablo, Alejandro; Suarez-Artacho, Gonzalo; Diez-Valladares, Luís; Santoyo-Santoyo, Julio; Martín-Pérez, Elena; Ausania, Fabio; López-Ben, Santiago; Jover-Navalon, José María; Garcés-Albir, Mariana; García-Domingo, Maria Isabel; et al. (Eselvier, 2019)
Objective: To compare the rates of R0 resection in pancreatoduodenectomy (PD) for pancreatic and periampullary malignant tumors by means of standard (ST-PD) versus artery-first approach (AFA-PD). Background: Standardized histological examination of PD specimens has shown that most pancreatic resections thought to be R0 resections are R1. “Artery-first approach” is a surgical technique characterized by meticulous dissection of arterial planes and clearing of retropancreatic tissue in an attempt to achieve a higher rate of R0. To date, studies comparing AFA-PD versus ST-PD are retrospective cohort or case-control studies. Methods: A multicenter, randomized, controlled trial was conducted in 10 University Hospitals (NCT02803814, ClinicalTrials.gov). Eligible patients were those who presented with pancreatic head adenocarcinoma and periampullary tumors (ampulloma, distal cholangiocarcinoma, duodenal adenocarcinoma). Assignment to each group (ST-PD or AFA-PD) was randomized by blocks and stratified by centers. The primary end-point was the rate of tumor-free resection margins (R0); secondary end-points were postoperative complications and mortality. Results: One hundred seventy-nine patients were assessed for eligibility and 176 randomized. After exclusions, the final analysis included 75 ST-PD and 78 AFA-PD. R0 resection rates were 77.3% (95% CI: 68.4–87.4) with ST-PD and 67.9% (95% CI: 58.3–79.1) with AFA-PD, P=0.194. There were no significant differences in postoperative complication rates, overall 73.3% versus 67.9%, and perioperative mortality 4% versus 6.4%. Conclusions: Despite theoretical oncological advantages associated with AFA-PD and evidence coming from low-level studies, this multicenter, randomized, controlled trial has found no difference neither in R0 resection rates nor in postoperative complications in patients undergoing ST-PD versus AFA-PD for pancreatic head adenocarcinoma and other periampullary tumors
Keywords: Páncreas - Cáncer; Artery-first; Pancreatic cancer; Pancreatoduodenectomy; Periampullary tumors